PEMBERIAN ENDAPAN EFFLUENT LAND APPLICATION PABRIK KELAPA SAWIT PADA MEDIA PMK DI PEMBIBITAN UTAMA KELAPA SAWIT (Elaeis guinensis Jacq.) - Basuki '; Sukemi Indra Saputra; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to determine the effect of effluent land application on PMK media and determine the good deposition of effluent land application dose on the growth of oil palm seeds in main nursery. The design used in this research was Completely Randomized Design (CRD) with giving effluent deposition application consist of 6 treatments that A0 (Without effluent deposition application), A1 (dose of 0,5 kg/plant), A2 (dose 1,0 kg/plant), A3 (dose of 1,5 kg/plant), A4 (dose of 2,0 kg/plant) and A5 (dose of 2,5 kg/plant). Parameters measured were the increase of plant height, number of leaves, leaf length, stump diameter and leaf area. Data obtained were analyzed using analysis of variance, then further tested using Honestly Significant Difference (HSD) at 5% level. Results of research shows giving the deposition effluent application for PMK planting media significantly effected on all parameters measured of oil palm seeds with the better treatment was dose of 2,0 kg/plant. Keywords: effluent land application, ultisol, oil palm.